Modelling and Prediction of Financial Stock Investment in India - Bhushan, Bharat (Gyan Management Journal, 2021)
The paper focuses on predicting investments in stock markets in India. Stock market investment continues to be popular because it is liquid, and has the potential for high returns when the stock market is not overly volatile. In order to provide a realistic and safe advice for investors, this study forecasts what the India stock market index will look like over the next month. Stock market performance is easily measured with the help of stock market indices. First, the data on the stock market index has non-stationary properties and was differenced using the ADF (Augmented Dickey fuller) approach to regularize it. ARIMA model is fitted to the series and there are five tentative ARIMAmodels which include ARIMA (1,2,1), ARIMA (2,2,1), ARIMA (3,2,5), ARIMA(4,2,4) and ARIMA (5,2,1) where ARIMA (1,2,1) is the best selected model because it has the least AIC and SBIC, the highestadjusted R-square and the least volatility. The best fitted ARIMA (1,2,1) was then used to forecast, and the forecast was good as it is constant over the predicted period, and there is no evidence of high volatility cluster, which suggest to investors to go ahead with investment as there is possibility of making huge profit and having good returns.